Structural identification of anthocyanins and analysis of concentrations during growth and flowering in buckwheat (Fagopyrum esculentum Moench) petals - Tatsuro, Suzuki; Kim, Sun-Ju; Sarker, Md. Zaidul Islam; Mukasa, Yuji; Shigenobu, Takigawa; Matsuura-Endo, Chie; Yamauchi, Hiraoki; Naoto, Hashimoto; Noda, Takahiro; Saito, Tatsuya (American Chemical Society, 2007)
The anthocyanin profiles and variety/breeding-line differences of anthocyanin concentrations in petals of common buckwheat flowers have been studied. Four anthocyanins, cyanidin 3-O-glucoside, cyanidin 3-O-rutinoside, cyanidin 3-O-rhamnoside, and cyanidin 3-O-galactosyl-rhamnoside were isolated from the petals of common buckwheat (Fagopyrum esculentum Moench), separated using high performance liquid chromatography and identified using reversed-phase liquid chromatography–electrospray ionization–tandem mass spectrometry techniques. In every variety/breeding line tested, cyanidin 3-Orutinoside was detected as the major anthocyanin and the next is cyanidin 3-O-glucoside whereas cyanidin 3-O-rhamnoside and cyanidin 3-O-galactosyl-rhamnoside were trace or not detectable in white and pink flowered buckwheat. Of all the varieties/breeding lines tested, Gan-Chao, a Chinese variety, contained the highest amount of anthocyanins. The largest part of cyanidin moiety was presented as a proanthocyanidin form (PAs–Cy). Anthocyanins and PAs–Cy in petals were increased along with increase of flower development stages. Therefore, fully developed petals of red flowered buckwheat, especially Gan-Chao, are promising as a new anthocyanin-rich material for food processing.